Separation of anaesthetic ketamine and its derivates in PAMAPTAC coated capillaries with tuneable counter-current electroosmotic flow - Tůma, Petr; Koval, Dušan; Sommerová, Blanka; Vaculín, Šimon (Talanta, 2020)
Capillary electrophoretic separation of ketamine, norketamine, hydroxynorketamine, and dehydronorketamine was performed in the counter-current regime under the influence of oppositely-directed electroosmotic flow. For this purpose, the fused silica capillaries were covalently coated with the poly(acrylamide-co-3-acrylamidopropyl trimethylammonium chloride) copolymer (PAMAPTAC). The content of the cationic monomer APTAC in the polymerization mixture varied in the range 0-6 mol. % and the generated electroosmotic flow increased continuously in the 0-20 · 10-9 m2V-1s-1 interval. Importantly, it resulted in improved electrophoretic resolution of ketamine/norketamine, which increased from 0.8 for neutral PAM coating (i.e. 0% PAMAPTAC) to 3.0 for 6% PAMAPTAC. The determination of ketamine and its derivates in rat serum was performed in a 4% PAMAPTAC capillary with an inner diameter of 25 μm. The separation was performed in a 500 mM aqueous solution of acetic acid (pH 2.3). The clinical sample was deproteinized by the addition of acetonitrile to the serum and a large volume of the treated sample was injected directly into the capillary. The achieved limit of detection ranged from 2.2 ng/mL for dehydronorketamine to 4.1 ng/mL for hydroxynorketamine; the intra-day repeatability was 1.0-1.5% for the migration time and 2.8-3.3% for the peak area. The developed methodology was employed for time monitoring of ketamines in rat serum after intra venous administration of low doses of anaesthetic at a level of 2 μg per g of body weight.
Keywords: Contactless conductivity detection; Clinical analysis; Capillary electrophoresis; Stacking; Peak master; Coating